Exploring learning needs for general practice based pharmacist: Are behavioural and influencing skills needed? - Johnson, Chris F. (Pharm Pract (Granada), 2020)
BACKGROUND: Embedding pharmacists in general practice has been shown to create cost efficiencies, improve patient care and free general practitioner capacity. Consequently, there is a drive to recruit additional pharmacists to work within general practices. However, equipping pharmacists with behaviour and influencing skills may further optimise their impact. Key elements which may enhance behaviour and influencing skills include self-efficacy and resilience. OBJECTIVE: This study aimed to: 1) Assess general practice pharmacists’ self-efficacy and resilience. 2) Explore differences primarily between pharmacists reporting lower and higher self-efficacy, secondarily for those reporting lower and higher scores for resilience. METHODS: All 159 NHS Greater Glasgow and Clyde general practice pharmacists were invited to complete an online survey in May 2019. The survey captured anonymised data covering: demographics; professional experience; qualifications, prescribing status and preferred learning styles. Unconscious learning needs for behavioural and influencing skills were assessed using validated tools: the new general self-efficacy scale (GSES) and short general resilience scale (GRIT). Participants’ responses were differentiated by the lowest quartile and higher quartiles of GSES and GRIT scores, and analysed to identify differences. RESULTS: The survey was completed by 57% (91/159) of eligible pharmacists; mean age 38 (range 24-60) years; 91% were of white ethnicity and 89% female. The median time qualified was 14 (1-38) years and 3 (1-22) years working in general practices. Overall pharmacists scored well on the GSES, mean 25 (SD 3; 95%CI 24.4-25.6), and GRIT, mean 30 (SD 4; 95%CI 29.6-30.4), out of a maximum 32 and 40 respectively. A significant positive correlation between GSES and GRIT scores was found (Pearson’s r=0.284, p=0.006). However, no significant differences were identified between pharmacists scoring in the lower and upper quartiles by GSES or GRIT. Overall respondents reported their preferred learning styles were activists (46%) or pragmatists (29%). The majority (91%) preferred blended learning methods as opposed to 38% or less for a range of online methods. CONCLUSIONS: General practice pharmacists on average scored highly for self-efficacy and resilience. Higher scores did not appear to be associated with demographic, years of practice, professional or educational experience. Prospective interventions to support those with lower scores may enhance and optimise pharmacists’ effectiveness in general practice.